2010
DOI: 10.1021/ja101476b
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Synthesis of Zinc Blende CdTe/CdS Magic-Core/Thick-Shell Tetrahedral-Shaped Nanocrystals with Emission Tunable to Near-Infrared

Abstract: We demonstrate the synthesis of near-IR-emitting zinc blende CdTe/CdS tetrahedral-shaped nanocrystals with a magic-sized (approximately 0.8 nm radius) CdTe core and a thick CdS shell (up to 5 nm). These high-quality water-soluble nanocrystals were obtained by a simple but reliable aqueous method at low temperature. During the growth of the shell over the magic core, the core/shell nanocrystals change from type I to type II, as revealed by their enormous photoluminescence (PL) emission peak shift (from 480 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 14 publications
9
96
1
Order By: Relevance
“…Remarkably, the extent of such band gap increase ($2 eV) is significantly higher than what has been achieved by the smallest colloidal QDs reported to date ($1 eV) (72,(117)(118)(119)(120). Compared with the colloidal II-VI quantum dots, the crystalline nanostructured hybrid semiconductors are free of several crucial issues [e.g., particle size distribution and morphology, postsynthetic purification, stoichiometric lattice (problems with lattices altered by the defects, e.g., excess atoms, alloying additions, or vacancies), local oxygen concentrations, as well as the dispersity of particles].…”
Section: Structure-induced Quantum Confinement Effectmentioning
confidence: 67%
See 1 more Smart Citation
“…Remarkably, the extent of such band gap increase ($2 eV) is significantly higher than what has been achieved by the smallest colloidal QDs reported to date ($1 eV) (72,(117)(118)(119)(120). Compared with the colloidal II-VI quantum dots, the crystalline nanostructured hybrid semiconductors are free of several crucial issues [e.g., particle size distribution and morphology, postsynthetic purification, stoichiometric lattice (problems with lattices altered by the defects, e.g., excess atoms, alloying additions, or vacancies), local oxygen concentrations, as well as the dispersity of particles].…”
Section: Structure-induced Quantum Confinement Effectmentioning
confidence: 67%
“…As shown in Table VIII, the thickness of the II-VI single layers in hybrid structures is typically $4-5 A , which is much smaller than the average dimensions of colloidal QDs. Thus, the extent of quantum confinement in hybrids (except for Mn based and double-layered structures) is evidently much stronger than that found in the smallest QDs reported to date (72,(117)(118)(119)(120)178). Theoretical calculations using density functional theory (DFT) with local density approximation (LDA) have been carried out on selected hybrid structures to confirm this observation (179,180).…”
Section: A Band Gaps and Optical Propertiesmentioning
confidence: 82%
“…[68][69][70] The possible exception is the aqueous synthesis of CdTe QDs, where quantum yields have been reported to reach 82% but are typically closer to 40%. [71][72][73] These QDs can also be relatively monodisperse, with FWHM values typically in the range of 30-60 nm.…”
Section: Quantum Dot Materialsmentioning
confidence: 99%
“…As a comparison, for Rhodamine B dye dissolved in methanol, the  values decreased from 0.8 to ~0.1 with increasing concentration in the range of ~10 -5 -10 -3 molar (Bindhu et al, 1996). For CdSe/ZnSe core/shell nanocrystals suspended in organic solvents, the values of = (0.60-0.85) were obtained, as a result of the thicker deposit shell concentration (Reiss et al, 2002); quantum yield values were reported as 0.4-0.6 for CdSe QDs (core-sizes between 2.8 and 5.0 nm), 0.55 for CdSe/ZnSe/ZnS (Donegá et al, 2006) and up to 0.70 for CdTe/CdS MSNs aqueous colloidal solution (Deng et al, 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The colors of the solutions are illustrative. (Chen et al, 2008;Deng et al, 2010), and the value of < em >= 588.9 nm for = 1.25 cm -1 at 514.5 nm was obtained from fluorescence measurement. Peaks related to longitudinal optical phonons (LO) and (2LO) at 206.6 and 411 cm −1 of the synthesized CdSe MSNs are clearly observable in the Raman spectrum shown in Fig.…”
Section: Spectroscopic Characterization Of Core-shell Qdsmentioning
confidence: 99%